Hydration structure and water exchange kinetics at xenotime–water interfaces: implications for rare earth minerals separation. Issue 15 (10th March 2020) - Roy, Santanu; Wu, Lili; Goverapet Srinivasan, Sriram; Stack, Andrew G.; Navrotsky, Alexandra; Bryantsev, Vyacheslav S.
Abstract : Multilayering of water molecules at the xenotime–water interface and heterogeneous water exchange timescales between these layers obtained by computing 2D-free energy landscapes and employing Marcus theory of solvent exchange. Abstract : Hydration of surface ions gives rise to structural heterogeneity and variable exchange kinetics of water at complex mineral–water interfaces. Here, we employ ab initio molecular dynamics (AIMD) simulations and water adsorption calorimetry to examine the aqueous interfaces of xenotime, a phosphate mineral that contains predominantly Y 3+ and heavy rare earth elements. Consistent with natural crystal morphology, xenotime is predicted to have a tetragonal prismatic shape, dominated by the 100 surface. Hydration of this surface induces multilayer interfacial water structures with distinct OH orientations, which agrees with recent crystal truncation rod measurements. The exchange kinetics between two adjacent water layers exhibits a wide range of underlying timescales (5–180 picoseconds), dictated by ion–water electrostatics. Adsorption of a bidentate hydroxamate ligand reveals that 100 xenotime surface can only accommodate monodentate coordination with water exchange kinetics strongly depending on specific ligand orientation, prompting us to reconsider traditional strategies for selective separation of rare-earth minerals.